(untitled) (Journal of the College of Education for Women, 2019)
That the child in the early years of his life learns a lot of experiences that help himgrow properly, and if the availability of the child family atmosphere full of love and affectionand trust he was able to grow healthy growth and is in accordance with itself and with thecommunity in which they live, and stop method of the child in the expression of fear on thenature of situation and on the theme of fear and the reaction of those around the child as wellas the vague positions that can not a child from its interpretation raises his fear, and its lead inlife are the kindergarten of the growing concerns him, causing his social concern, therefore,targeted current research to identify patterns of parental care(mothers), followed byparents(mothers) with their children and find differences in care depending on the type of sex(male, female) and find the relationship between patterns of parental care(mothers) and socialphobia at (300) children from the children Riyadh governmental and private organizations inthe city of Baghdad for the academic year (2011-2012) and the results indicate that the stylemost often used is to control and control and that this technique the most powerful fear ofsocial relationship.